USULAN PERBAIKAN TATA KELOLA TI PADA PROSES MENINGKATKAN ORIENTASI PELANGGAN & PELAYANAN BERDASARKAN COBIT 4.1 STUDI KASUS : STMIK KHARISMA MAKASSAR - Yulia Jinarto; Irfan A Palalloi; Hendra Surasa (STMIK KHARISMA Makassar, 2015)
Aim and purpose of this research is how the picture of the current state (as-is), and the expected conditions (to-be), in order to obtain the level of maturity of the application of IT Governance that have been and will be applied, and how to proposed strategy improvement. The method applied refers to the COBIT 4.1 framework, and focused on the evaluation process DS10 (Manage problems). Collecting data through interviews and questionnaires distribution to describe the current state (as-is), and the expected (to-be). Then, the measurement results of the questionnaire using the reliability test and validity test. Results from this study indicate the level of maturity of current state (as-is) in each attribute (AC, PPP, TA, SE, RA, GSM) at the level of 2 (two), and the expected conditions (to-be) were in level 4 (four); gaps in the overall attribute is 2 (two); and generate strategies proposed improvements, which at level 2 (repeatable but intuitive) to 3 (defined) focuses on documentation, understanding procedures, construction, and communications. Meanwhile, at level 3 to 4 (managed and measurable) focused on monitoring, maintenance, evaluation, and measurement.